Investigation on the influence of fluid accumulation in the exhaust pipe of infusion set on following fluid infusion (输液器排气管积液对后续液体影响的现状调查) - XIA Juanjuan (夏娟娟); ZHOU Yanqiong (周雁琼); SHU You (舒优) (Association of Integrative Nursing, 2021)
Objective To investigate the influence of fluid accumulation in the exhaust pipe of infusion set on following fluid infusion, and provide reference for the Standardization and security of infusion in clinical settings. Methods An online-survey was conducted to investigate the nurse's awareness of fluid accumulation in the exhaust pipe of infusion set, and a field survey of the usage of the exhaust pipe of infusion set and handling of fluid accumulation in the exhaust pipe was performed. Results According to the results of online-survey and field survey, it was an common issue that fluid accumulation in the exhaust pipe had been mixed with following infusion fluid, and observation was insufficient for monitoring the transparent fluid. Unsatisfactory results were reported in handling the fluid accumulation in the exhaust pipe. Conclusion Findings of the survey reveals an common issue of fluid accumulation in the exhaust pipe had mixed with following infusion fluid, and insufficient awareness on observing transparent fluid among nurses. Given the incompatibility caused by the mixed fluid, it is required to enhance the nurse awareness and handling skills on fluid accumulation in the exhaust pipe. (目的 讨论输液器排气管积液对后续输液的影响, 为临床输液规范化、安全化提供重要依据。方法 采用线上问卷调查综合医疗科护士队输液器排气管积液现象的认知, 同时针对科室需排气管液体使用情况和排气管积液处理情况进行线下调查。结果 综合医疗科护理人员在需排气管辅助输液过程中, 广泛存在输液器排气管积液反流并与后续液体混合的情况, 而且多数护理人员只关注有颜色的积液对后续液体的影响, 缺乏对排气管中无色液体对后续液体影响的观察, 部分护理人员对排气管积液处理结果不理想。结论 输液器排气管积液广泛存在, 而护士的关注程度不高, 处理不够积极且处理结果不够理想。药物混合存在相关药物配伍禁忌的风险, 应该加以重视和改进。)